2023
DOI: 10.3389/fpubh.2023.1205903
|View full text |Cite
|
Sign up to set email alerts
|

Patent analysis of digital sensors for continuous glucose monitoring

Abstract: The high need for optimal diabetes management among an ever-increasing number of patients dictates the development and implementation of new digital sensors for continuous glucose monitoring. The purpose of this work is to systematize the global patenting trends of digital sensors for continuous glucose monitoring and analyze their effectiveness in controlling the treatment of diabetes patients of different ages and risk groups. The Lens database was used to build the patent landscape of sensors for continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Furthermore, Litvinova et al attempted to systematize the global patenting trends of digital sensors for CGM and analyze their effectiveness in controlling the treatment of patients with diabetes of different ages and risk groups. 36 The LENS database was used to build the patent landscape of sensors for CGM. A retrospective analysis showed that the patenting of sensors for CGM had a positive trend over the analyzed period (2000–2022).…”
Section: Highlights Of the Literaturementioning
confidence: 99%
“…Furthermore, Litvinova et al attempted to systematize the global patenting trends of digital sensors for CGM and analyze their effectiveness in controlling the treatment of patients with diabetes of different ages and risk groups. 36 The LENS database was used to build the patent landscape of sensors for CGM. A retrospective analysis showed that the patenting of sensors for CGM had a positive trend over the analyzed period (2000–2022).…”
Section: Highlights Of the Literaturementioning
confidence: 99%
“…Another drawback is the accuracy, where the Mean Absolute Relative Difference (MARD) was 18.1%, 91.1% of data points fell in zone A, and 7.8% in zone B of the Clarke error grid (CEG) analysis 20 . Similarly, the glucometer by Helo Extense World Global Network takes into account external factors such as temperature variability, and the effect of pressure and sweat to measure blood glucose and has not been approved by the FDA 21 , 22 . Likewise, the glucometer by Wizmi, WEAR2B Ltd is under clinical trial, where a study obtained 93% in zone A and 7% in zone B in CEG 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the glucometer by Helo Extense World Global Network takes into account external factors such as temperature variability, and the effect of pressure and sweat to measure blood glucose and has not been approved by the FDA 21 , 22 . Likewise, the glucometer by Wizmi, WEAR2B Ltd is under clinical trial, where a study obtained 93% in zone A and 7% in zone B in CEG 22 , 23 . A discussion of commercial devices in areas other than optical methods is presented in I2, Supplementary Material 1.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal hyperglycemia during pregnancy has been shown to increase the risk for several adverse pregnancy outcomes including stillbirth, congenital malformations, admission to a neonatal intensive care unit, a low APGAR score and large-for-gestational-age babies [1][2][3][4][5][6]. Despite the fact that modern technology for blood glucose monitoring and insulin management is becoming a more central part of treating diabetes, the frequencies of adverse pregnancy outcomes remain significantly higher in babies born of women with diabetes and the rate of babies being born large for gestational age is increasing [7][8][9]. In addition, the overall incidence of pregnancies complicated by maternal diabetes is increasing significantly, making this a relevant concern for today's healthcare professionals [3,10,11].…”
Section: Introductionmentioning
confidence: 99%